Pengaruh Profitabilitas Dan Leverage Terhadap Pengungkapan Emisi Karbon Serta Dampaknya Terhadap Harga Saham - Irma Sri Lestari; Dwi Indah Lestari (Universitas Serang Raya, 2024)
This study aims to determine the effect of Profitability and Leverage on Carbon Emissions Disclosure and Their Impact on Stock Prices focusing on Non Finance companies listed on Indonesia Stock Exchange for the Year 2012-2020 2012-2020. The research used quantitative research methods with sampling using purposive sampling method with a sample of 14 companies and 9 years of observation so that the sample obtained as many as 126 samples. The data used in this study is secondary data in the form of annual reports and sustainability reports of each company. The analytical tool in this study used path analysis. The results of this study indicated that profitability and leverage had no effect on the carbon emission disclosure, profitability directly had a positive effect on stock price, while leverage directly had a negative effect on stock prices, and carbon emission disclosure had no effect on stock prices. Profitability indirectly has no effect on stock prices by passing the carbon emission disclosure, while leverage indirectly has a negative effect on stock price by passing the carbon emission disclosure.